1995
DOI: 10.1017/s0043174500081509
|View full text |Cite
|
Sign up to set email alerts
|

Plant Responses to Light: A Potential Tool for Weed Management

Abstract: Light regulates many facets of plant growth and development through the effects of quantity of total energy and of photons, spectral quality, duration, and photoperiod. Numerous techniques and types of equipment are available for quantifying light in plant canopies. The effect of total quantity of light on weed and crop productivity has been described for many cropping systems. Recent work has focused on other aspects of light, in particular, spectral distribution of light (quality), transient light (sunflecks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
2
10

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(115 citation statements)
references
References 125 publications
1
97
2
10
Order By: Relevance
“…Phytochrome-mediated processes that allow plants to adjust their growth in response to changes in the ratio of red to farred light can affect the interaction of competing plants (Casal and Smith, 1989;Ballare et al, 1990;Holt 1995). The rapid height gain of E. oryzoides in California rice (Bayer and Hill, 1993) and the ability of the weed to adjust its height in response to its neighbours (Yamasue et al, 1997) may be related to light quality cues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytochrome-mediated processes that allow plants to adjust their growth in response to changes in the ratio of red to farred light can affect the interaction of competing plants (Casal and Smith, 1989;Ballare et al, 1990;Holt 1995). The rapid height gain of E. oryzoides in California rice (Bayer and Hill, 1993) and the ability of the weed to adjust its height in response to its neighbours (Yamasue et al, 1997) may be related to light quality cues.…”
Section: Discussionmentioning
confidence: 99%
“…Competition for light is an important component of the crop± weed interference (Holt 1995). Understanding how rice and weeds respond to shade may help researchers improve weed control strategies and also evaluate algorithms for the ecophysiological modelling of competition for light between weeds and irrigated rice (Kropff and van Laar, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these modern crop stands are nowadays probably too dark for many typical light-demanding arable weed species. Experimental evidence shows that many arable species grow best at high illumination (Bornkamm, 1961;Fitter and Ashmore, 1974;Holt, 1995). Tall-growing maize, the crop with the largest increase in cultivation area in Germany during the recent boost of energy farming (Steinmann and Dobers, 2013), reduces transmissivity to lower levels than the other three conventional crops, and the range of transmissivities measured was smaller in maize than in all other crops.…”
Section: Light Transmission Patterns In Different Cropping Systemsmentioning
confidence: 99%
“…It determines photosynthetic carbon gain and regulates developmental processes such as seed dormancy, germination, and photomorphogenesis (Ballaré and Casal, 2000;Holt, 1995). Over a broad range of light intensities, productivity increases linearly with the amount of absorbed photosynthetically active radiation (PAR,.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sowing cereal crops at wider row spacing resulted in increased competition within the crop plant clusters (i.e., the rows), resulting in decreased crop growth and yield compared with narrow row spacing (Shapiro and Wortmann, 2006). Holt (1995) suggested that manipulating the crop row spacing and orientation may reduce light interception by weeds. Crop shading via narrow row spacing can improve weed control without extra costs or negative environmental impacts (Barberi, 2002).…”
Section: Introductionmentioning
confidence: 99%